Comparative method with the use of laser scanning as a starting point for the assessment of the state of preservation of the face of the walls in the Kłodzko Fortress - Gleń, Piotr; Krupa, Karol (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2020)
This article presents architectural studies of the state of preservation of the face of the wall of the Kłodzko Fortress on the basis of the surveying works performed since 2016. These works include measurement of the entire fortress with the use of laser scanning. The analysis was carried out on the face of the wall, gradually degrading due to external factors and incorrect protection of the masonry. For detailed analysis, clouds of points from the period of 2 years (2017-2018) were used, taking into account the discussed northern part of the wall of the Great Tenaille (Wielkie Kleszcze). The paper explains the importance of the surveying process for the conservation works aiming at protection of the historical tissue from further degradation.